PENGARUH WAKTU PEMUPUKAN PHONSKA DAN JUMLAH BUAH PER TANAMAN TERHADAP HASIL TANAMAN MELON (Cucumis melo, L.) VAR. GLAMOUR - Raka Permana Siwi; Anjarwani Anjarwani; Tujiyanta Tujiyanta (Universitas Tidar, 2016)
Research on the effects of fertilization Phonska time and number of fruits per plant on yield of melon (Cucumis melo L.) var. Glamour conducted from May to July 2015 in the greenhouse Agriculture Department Magelang, jl. Cempaka no. 6 Magelang. Altitude of 360 m above sea level and type of latosol soil with a pH of 6. The experiment was conducted using a factorial design (3 x 3) are arranged in a complete randomized block design, repeated three times. The first factor is the time of fertilization Phonska: 7 days before planting, 0 days before planting (planting time), and 7 days after planting. The second factor is the number of fruits per plant: 1, 2, and 3 fruit / plant. The results showed that the time of fertilization Phonska not accelerate flowering age, harvesting age, and does not increase the weight, volume, diameter, thick fruit pulp and sugar melons. Treatment of the number of fruits per plant showed one fruit crop harvesting produce faster and per fruit weight, diameter, volume, thick flesh and blood sugar levels are higher than other treatments. While on treatment two fruits per plant produces fruit weight per plant were highest.